2013
DOI: 10.1089/zeb.2012.0819
|View full text |Cite
|
Sign up to set email alerts
|

Husbandry of Zebrafish, Danio Rerio, and the Cortisol Stress Response

Abstract: The effect of common husbandry conditions (crowding, social environment, water quality, handling, and background color) on the cortisol stress response in adult zebrafish, Danio rerio, was investigated to check the usefulness of zebrafish as a model organism in aquaculture research. In addition, a noninvasive methodology for assessing stress was evaluated. Zebrafish showed a fast cortisol response with high values at 30 min that returned to basal levels within 2 h of poststress. There was a significant positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
73
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 28 publications
5
73
0
Order By: Relevance
“…However, the most important aspect to consider is that the cortisol levels measured in our fish (<1 ng g −1 M b ) cannot be considered representative of a stressful situation, as reported values in zebrafish subjected to different types of stress (e.g. crowding, handling, visual predator) are much higher, in the range 4-12 ng g −1 (Ramsay et al, 2006;Barcellos et al, 2007;Pavlidis et al, 2013). The lack of a cortisolrelated stress response has been documented in other species such as the gilthead sea bream, Sparus aurata (Barton et al, 2005), and the wedge sole, Dicologoglossa cuneate (Herrera et al, 2015), suggesting that acclimation to a chronic stressor allowed the attenuation of cortisol release, which is more related to the acute rather than the chronic stress response.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, the most important aspect to consider is that the cortisol levels measured in our fish (<1 ng g −1 M b ) cannot be considered representative of a stressful situation, as reported values in zebrafish subjected to different types of stress (e.g. crowding, handling, visual predator) are much higher, in the range 4-12 ng g −1 (Ramsay et al, 2006;Barcellos et al, 2007;Pavlidis et al, 2013). The lack of a cortisolrelated stress response has been documented in other species such as the gilthead sea bream, Sparus aurata (Barton et al, 2005), and the wedge sole, Dicologoglossa cuneate (Herrera et al, 2015), suggesting that acclimation to a chronic stressor allowed the attenuation of cortisol release, which is more related to the acute rather than the chronic stress response.…”
Section: Discussionmentioning
confidence: 95%
“…Surprisingly, and opposite to what happens with rodents, where universal husbandry protocols are available, the zebrafish community lacks universal rearing guidelines. Although many authors have focused on the different aspects of rearing conditions (Westerfield, 1995;Casebolt et al, 1998;Trevarrow, 2004;Lawrence, 2007;Pavlidis et al, 2013;Giacomini et al, 2015), a main variable such as rearing density is still not clearly established. Thus, it is urgent to clarify the influence of rearing density on zebrafish sex differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…The zebrafish is a relatively new model in genetics and brain-behaviour research and differences between strains of zebrafish (Egan et al, 2009;Vignet et al, 2013;Wahlsten et al, 2006) as well as rearing conditions within and between laboratories (Mahabir et al, 2013;Parker et al, 2012;Pavlidis et al, 2013) may affect the outcome of experiments. Our data strongly suggest that at a behavioural and physiological level the UCS protocol is robust and reproducible in decreasing inhibitory learning and elevating whole-body cortisol content across strains of zebrafish, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is challenging to unravel the specific cause underlying acclimation time effects, wild fish during development may undergo confinement stress with an increase in the cortisol stress hormone, a well-documented occurrence in teleost fishes (Barton and Iwama, 1991;Bonga, 1997). Furthermore, previous studies have shown that laboratory conditions, such as tank color and densities of fish held together, can affect behavior and physiology (Brown et al, 1992;Pavlidis et al, 2013;Hasenbein et al, 2016). For example, when held in lower densities, Arctic char (Salvalinus alpinus) exhibited altered swimming behavior and more aggressive interactions (Brown et al, 1992).…”
mentioning
confidence: 99%